GEOCHEMISTRY OF ANCIENT OPHIOLITES OF THE SHARYZHALGAI UPLIFT - Gladkochub D.P.; Sklyarov E.V.; Men'shagin Yu.V.; Mazukabzov A.M. (My University, 2001)
Petrological, geochemical, and geochronological data for the basic-ultrabasic rocks of the Bulun block from the Sharyzhalgai uplift are reported, and the age and geodynamic environments of these geologic structures are determined. The examined rocks are determined to be fragments of a reduced ophiolitic sequence, which included relics of a residual and a gabbroid complex. The metamorphosed ultramafic rocks of the residual complex exhibit petrochemical characteristics corresponding to those of the Fe-rich peridotites of mid-oceanic ridges and backarc spreading zones. The gabbroid complex is determined to consist of metapyroxenites, gabbro-pyroxenites, and metagabbroids. All of the metabasic rocks affiliate with the tholeiite series. The gabbro-pyroxenites correspond to N-MORB, whereas the metagabbroids are geochemically similar to T-MORB. Based on a complex of geological, petrological-geochemical, and isotopic-geochemical criteria, a conclusion is drawn that the fragment of the metamorphosed mafic-ultramafic rock association of the Bulun block from the Sharyzhalgai uplift should be classified with Early Precambrian ophiolites.
Keywords: Precambrian; Precambrian; Докембрий